Evaluating Barriers to Adherence to Dietary Recommendations in Iranian Adults with Metabolic Syndrome: A Qualitative Study Using the Theory of Reasoned Action - Naseh ESMAEILI; Mohammad ALIZADEH; Ali TARIGHAT ESFANJANI; Sorayya KHEIROURI (Tehran University of Medical Sciences, 2016)
Background: Metabolic syndrome (MS) is defined as a pattern of metabolic disorders including central obesity, insulin resistance or hyperglycemia, high blood pressure, and dyslipidemia. Many studies show a clear relationship between diet and components of MS. The aim of the current study was to identify barriers to adherence to dietary recommendations among Iranian MS patients. Methods: The theory of reasoned action (TRA) served as the framework for this qualitative study. Data collection was conducted through six semi-structured focus group discussions, from Apr to Jun 2013. Subjects included 36 married men and women with different levels of education between the ages of 20-50 with MS diagnosed based on IDF's (International Diabetes federation) criteria. All focus group discussions were audio recorded and transcribed. The thematic content analysis method was used to analyze the study data. Results: This study identified the most important barriers to adherence to dietary recommendations. MS patients have problems in their attitude toward MS components and their relationship to nutrition. They also had wrong attitudes toward fats and oils, salt, dairy products, cereals, and sugary drinks and sweets. Subjective norms that affects patient eating identifies too. Conclusion: We identified barriers to adherence to dietary recommendations in MS patients that could be used to prevent MS consequences and provide patients with nutrition education.   Keywords: Metabolic syndrome, Theory of reasoned action, Dietary recommendations, Barriers